WGA guidelines on design and reporting of glaucoma surgical trials - Shaarawy, Tarek; Grehn, Franz; Sherwood, M. (Kugler Publications, 2009)
It is evident that in the last couple of years there has been a surge of interest in research in the fi eld of glaucoma surgery. This includes research in the improvement of conventional glaucoma surgery; trabeculectomy, and glaucoma drainage devices, as well as research in more recently introduced surgical methods and their emplacement in our range of surgical therapeutic options. Modulation of wound healing, a factor of paramount importance, has also received its share of research interest. More recently, research has embarked on identifying different surgical approaches and alternative surg.